Dream Angus : [compact disc, unabridged] : the Celtic god of dreams - McCall Smith, Alexander, 1948- (Brilliance Audio, 2006)
In a retelling of an ancient Celtic myth about Angus, the god of love, youth and beauty, who turns one's romantic dreams upside down; five young men named Angus parallel the god's story as they search for true love.